Places That Frighten: Residues of Wealth and Violence on the Argentine Chaco Frontier - Gordillo, Gastón (Anthropologica, 2022)
On the old frontiers of the Gran Chaco plains in north west Argentina, people in rural areas argue that some of the overgrown ruins that dot the regional landscape have the power to "frighten" (asustar), usually through the presence of ghosts, apparitions, or unusual sounds and lights. In this article, I aim to show that these experiences of fear contain important clues to the way local criollos (non-indigenous settlers of racially mixed background) spatialize their social memory. I analyze how the spatiality of these frightening presences is grounded on the vestiges of Jesuit missions, Spanish forts and colonial set tlements that evoke the history of conquest that constituted the regional geography. In particular, I examine how criollo perceptions of these sites revolve around imaginaries of the wealth that allegedly characterized the region in the past and the violence once unleashed on "the Indians" who used to live there.